A low-cost approach to upskilling tutors in frontline health care worker production value chain - Anddy Omoluabi; Linda Ugalahi; Olufolake Akeju; Emmanuel Aiyenigba (AOSIS, 2024)
Nigeria, like many countries, struggles with a shortage of healthcare professionals including frontline healthcare providers at the primary healthcare (PHC) level. While the country is pitched towards producing more healthcare professionals, the existing infrastructure to produce them is inadequate. Producing healthcare professional with the required skills to deliver quality services is impeded by several factors including the use of outdated curricula for their training, low application of technology in teaching, and weak tutor capacity that is worsened by the paucity and high cost of opportunities for tutor continuing professional development. To address these issues, the Health Workforce Management Activity (HWM), an initiative of the United States Agency for International Development (USAID), in 2023 designed and implemented a low-cost programme called TutorConnect that offered low-cost continuing professional development to tutors. TutorConnect is a Zoom-based monthly training programme that is facilitated by subject matter experts. The programme offered topics spanning effective learning, enhanced instructional design, and improved student engagement in the 14 months of its operation with over 700 tutors from more than 10 states in Nigeria that benefited from it. Utilising WhatsApp for additional support and peer-to-peer learning was crucial to providing more hands-on support, and institution-specific solutions. This low-cost approach to build competencies enabled access to continuing professional development by tutors, limiting effects of location and finances as barriers to continuing professional development. Developing the teaching capacity of tutors is pivotal to enhancing the quality of frontline healthcare worker training.